The necessity for hand therapy interventions for patients with partial thickness isolated hand/forearm burns: A randomized controlled pilot trial - Bradley J. Schmitt; Kathy Stiller; Kathryn E. Heath; Tanja Klotz; John E. Greenwood (Elsevier, 2018)
Objective: The recovery of patients with partial thickness isolated hand burns managed with an epidermal skin substitute appears to be rapid and the necessity for routine hand therapy interventions in this setting is unknown. This study investigated the need for hand therapy for these patients. Methods: A randomized controlled trial was undertaken. The Treatment Group received routine hand therapy provided by a physiotherapist, including assessment, daily range of motion exercises, education and, if required, edema management and outpatient physiotherapy follow-up. Control Group participants received no hand therapy input. Outcomes included the Michigan Hand Questionnaire (baseline, 1, 2, 4 weeks and 3 months post-injury), finger total active motion, wrist range, grip strength (1, 2 and 4 weeks) and participant satisfaction (4 weeks). Results: Twenty-nine participants were recruited over a 2.3 year period. All outcomes significantly improved over time (p ≤ 0.008). No significant between-group differences were observed for any outcome except the pain subscale of the Michigan Hand Questionnaire. Participants with deeper burns had significantly poorer outcomes for some Michigan Hand Questionnaire data. Study limitations included a small sample size, heterogeneity and some loss to follow-up. Conclusions: While the provision of routine hand therapy interventions for patients with partial thickness isolated hand/forearm burns that were managed with an epidermal skin substitute did not appear to be of benefit, study limitations means these results cannot be extrapolated and reinforces the need for further research. Routine hand therapy input may be of benefit for those with deeper burns. Keywords: Burns, Skin, Artificial, Physical therapy modalities, Hand, Injuries